Directions for cost and outcome analysis of Starting Early Starting Smart : summary of a cost expert meeting - Cannon, Jill S.; Karoly, Lynn A., 1961-; Kilburn, M. Rebecca; Rand eBooks (Santa Monica, CA : RAND, 2001)
In August 2000, RAND convened a meeting of national experts to discuss issues surrounding cost-benefit and related analyses of Starting Early Starting Smart (SESS), a public/private initiative led by the Casey Family Programs (CFP) and the Office on Early Childhood, Substance Abuse, and Mental Health Services Administration (SAMHSA). SESS compares the effectiveness of integrated behavioral health care--such as mental health services and substance abuse treatment and prevention--for children age 0 to 7 and their families with outcomes for those who receive the usual standard of community care. As part of the planning for a second phase of the SESS program, CFP and SAMHSA sought information on how to collect and analyze cost data for the program, and retained RAND to bring together experts to discuss incorporating cost-benefit analysis into the new design. This book summarizes the major topics under discussion at that meeting, including SESS program benefits, costs, and performance measurement challenges, and potential design issues for future SESS program planning and evaluation.
"Labor and Population Program."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Starting Early Starting Smart (Program) -- Cost effectiveness -- Congresses; Child mental health services -- United States -- Cost effectiveness -- Congresses; Child welfare -- United States -- Cost effectiveness -- Congresses; Children -- Substance use -- United States -- Congresses; Early childhood education -- United States -- Cost effectiveness -- Congresses; Electronic books